Physiotherapy Students' Attitudes Toward Working With People With Dementia: A Cross-Sectional Survey. (2nd January 2020) - Hunter, Susan W; Armstrong, Jessica; Silva, Mark; Divine, Alison
Abstract: Aims : To understand personal, educational and clinical experiences and the attitudes of physiotherapy students towards people with dementia. Methods : Online survey questionnaire. Physiotherapy students in the last year of a two-year Masters of Physical Therapy (MPT) entry-to-practice degree program ( n = 59) were surveyed. Descriptive statistics were used to analyze the data. Results: Fifty-five students participated (93%). The majority of students ( n = 52/55, 77%) had at least one clinical placement working with people with dementia. Overall, 53% ( n = 29/55) felt their academic training was sufficient to effectively work with people with dementia. Moreover, 82% ( n = 45/55) reported their confidence was greatest working with people who could communicate well verbally. Conclusions: Disease-based knowledge was strong, yet just over half felt their academic training was sufficient to effectively work with people with dementia. The findings support the need for more training, particularly in communication strategies, to support students to effectively work with client with dementia upon graduation.